1953
DOI: 10.1098/rspa.1953.0125
|View full text |Cite
|
Sign up to set email alerts
|

The activities of evaporated metal films in gas chemisorption

Abstract: The interaction of N 2 , H 2 , CO, C 2 H 4 , C 2 H 2 and O 2 with clean evaporated films of some twenty metals has been investigated between 0 and – 183° C. The results are expressed as gas chemisorbed or gas not chemisorbed. O 2 chemisorption is universal among all the metals studied, with the single exception of Au. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1962
1962
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Following the argument that the filled d-band of silver prevents interaction with H 2 [32,33,65], one may in turn suspect that silver that interacts with dihydrogen is characterized by structural defects at the surface or impurities that alter the electronic situation. The activated species from H 2 and D 2 on the silver surface must have opportunity to react with each other, which may arise because they are retained on the surface long enough while having sufficient mobility, or because the coverage is significant.…”
Section: Activation Of Dihydrogenmentioning
confidence: 99%
“…Following the argument that the filled d-band of silver prevents interaction with H 2 [32,33,65], one may in turn suspect that silver that interacts with dihydrogen is characterized by structural defects at the surface or impurities that alter the electronic situation. The activated species from H 2 and D 2 on the silver surface must have opportunity to react with each other, which may arise because they are retained on the surface long enough while having sufficient mobility, or because the coverage is significant.…”
Section: Activation Of Dihydrogenmentioning
confidence: 99%
“…Furthermore, there was a definite, measurable increase in CO at filament change on day 286 of 1969, thus indicating the continuing importance of CO. Finally, previous laboratory work on surface interactions (Trapnell, 1953) indicates that gold is the least reactive of all metals and N 2 the least reactive molecule (except for the noble gases) on any metal, whereas CO is known to chemisorb on gold.…”
Section: Molecular Nitrogen Densitymentioning
confidence: 99%
“…Desorption of atomic oxygen is included to explain the finite atomic oxygen source density at apogee. The interaction of molecular oxygen with the surfaces is ignored, and recombined oxygen is assumed to appear immediately in the gas phase, because molecular oxygen is not expected to chemisorb on gold (Trapnell, 1953;Wood, Baker, and Wise, 1970) and would thus have a very short surface interaction time.…”
Section: Atomic Oxygen Densitymentioning
confidence: 99%
“…These low heats of adsorption allow the adsorption process to be reversible and Trapnell [56] shows that at low pressures and room temperature, the light hydrocarbons desorb with no measurable, i.e., less than 2% coverage at pressures less than 10-' Torr.…”
mentioning
confidence: 99%
“…Surface steps did not playa critical role in the adsorption properties of gold, in contrast to that of the similar chemical material, platinum. Earlier work by Trapnell [56] using polycrystalline gold films showed that reversible molecular adsorption of CO, C,H" C 2 H 2 , and other light hydrocarbons did occur with low heats of adsorption (0.4 eV Imolecule) for high pressures.…”
mentioning
confidence: 99%